The evolution of competition laws and their enforcement : a political economy perspective - Mehta, Pradeep S. (New York : Routledge, 2012)
'This edited volume identifies the various country specific factors that warrant changes in the design and implementation of competition laws. The book covers case studies of nine countries of differing sizes and at varying stages of economic development, that have at one stage or another repealed extant competition laws for new ones, and seeks to examine the motivations and contexts under which this was done. The countries examined include the Czech Republic, Hungary, India, Ireland, Poland, Serbia, South Africa, Tanzania and the UK. Tracing the evolution of competition regimes in the countries covered, the book provides lessons for countries still in the process of forming their competition regimes. The contributions show that the road to strong competition regimes is seldom smooth, and that social, economic and political factors in the country hugely impact on the pace and effectiveness of competition reforms. The volume also addresses the issue of when the development of competition policies and laws can be seen to be in conflict with national development strategies. This book will be extremely useful for academics and students in the fields of global competition, law and economics, and development economics, as well as for policymakers. Pradeep S. Mehta is the founder Secretary General of Consumer Unity & Trust Society (CUTS), a leading economic policy research, advocacy and networking organisation, and serves on several policy-making bodies of the Government of India, related to trade, investment, competition, environment and consumer affairs'--
Adoption and reform of competition laws and their enforcement : a cross-country perspective / Vivek Ghosal and Siddhartha Mitra -- The Czech Republic's experience with competition policy and law / Sonia Gasparikova -- The development of the Hungarian competition law : from the outset (1991) until 2007 / Jozsef Sarai and Gabor Szoboszlay -- Evolution of competition policy and law in India / S. Chakravarthy -- Boston v Berlin : a half century of Irish antitrust / Patrick M. Lyons, Patrick Massey, and Moore McDowell -- Evolution of the competition law and competition policy in Poland / Tomasz Odziemczyk -- Competition law and policy in Serbia in the context of the EU accession process / Slavica Penev and Sanja Filipovic -- The evolution of competition policy and law in South Africa / Nandi Mokoena -- Why do countries adopt competition laws : the Tanzanian case / Fredrick S. Ringo -- The evolution of competition law and policy in the UK / Andrew Scott.
'Simultaneously published in the USA and Canada'--T.p. verso.
Includes bibliographical references and index.
Keywords: Antitrust law